The Carcinogenicity of Smokeless Tobacco- Are the Young People Aware - Zain Ul Abideen ,Syed Arshad Sabir,Jawad Zahir,Tabish Hussain, Hyna Fatima Hina Farooq,Amina Elahi,Abdullah Abbasi (Journal of Rawalpindi Medical College, 2013)
Background: To determine the awareness regarding the carcinogenicity of smokeless tobacco products(SLT) amongst adolescents and youth and identify potential predisposing factors associated with poor awareness. Methods: This cross sectional study included adolescents and youth age groups (10-24 years of age) A self designed questionnaire was used to interview 423 respondents who visited medical and surgical OPDs. Information was collected upon demographic variables in addition to the awareness, family use and use of smokeless tobacco. Perception about carcinogenicity of tobacco was analyzed in relation to gender and educational status Results: The mean age of the respondents and users was 21 and 21.6years respectively. Seventy eight (18.44%) users of SLT were identified. Majority (95.6%) were aware of SLT use in the area and greatest awareness was about Niswar (90%). Majority (82.5%) considered SLT harmful for health. Awareness about carcinogenicity of tobacco was statistically high (OR=3.09) in educated subjects. In 61.5% family use of SLT was present. The most common sources of knowledge were social contacts (60%). Most (68.8%) respondents considered SLT less harmful then smoking. Conclusion: Awareness regarding carcinogenic effects of SLT is inadequate.